Effect of annealing on microstructure and mechanical properties of biomedical hot-rolled Co-Cr-W-Ni alloy. (13th November 2019) - Zhu, Ziyi; Chen, Leng
Abstract: In the present study, the microstructural evolution and mechanical properties of hot-rolled biomedical Co-20Cr-15W-10Ni (wt%) alloy were investigated. The hot-rolled alloys were acquired and annealed at 600 °C–1000 °C for 10 min–24 h. The experimental results show that the microstructural evolution primarily contains two aspects: precipitation of carbides and intersections of stacking faults. The formation of M7 C3, M23 C6 and M6 C carbides was detected in the annealed alloys using x-ray diffraction. The evidence that M23 C6 carbides decomposed and precipitated M6 C carbides in situ was also discovered. Notably, a small amount of M6 C carbides precipitated on the twin boundaries when annealed at 1000 °C for 24 h, which is believed to suppress the strain induced martensite transformation (SIMT) process. The resistance force to the dislocation motion caused by the intersections of stacking faults was estimated to 0.78 N m −1 by using a geometric model. A high tensile strength of 1200 MPa with an excellent elongation of 50% was acquired when the alloys were annealed at 1000 °C for 24 h, although a large number of carbides precipitated on the grain boundaries. Alloys with these features can be a suitable candidate for hot extrusion for manufacture of stents and other biomedical parts in human body.